E-logistic: an information perspective / Ahmad Munawir Mohammed - Mohammed, Ahmad Munawir (2000)
Logistics is unique and despite its enormous contribution to our economic activities it is the least understood industry. Logistics is a military term and concepts but. currently logistics have been implemented and used in the commercial activities to move products and services where and when they are required. Logistics plays an important role especially in the manufacturing and retailing industry where competition is stiff. Hence, it is not surprising to note that many companies are scrutinizing on their logistics operation not only as a means to reduce production costs but to gain competitive advantage over their competitors and to improve their customer service levels. These objectives can only be achieved through excellent logistics information system because information is very important ingredient in logistics activities. A good information system that collect, maintain and distribute all forms of logistics information can be considered as the backbones of logistics operations. The advancement in the information and communication technology has resulted in the introduction of electronics in almost every aspect of the logistics operations. This paper attempts to highlight the importance and role of information in logistics including the impact of electronic applications in the present day logistics industry.